Hydrogen Sulfide Alleviates Waterlogging-Induced Damage in Peach Seedlings via Enhancing Antioxidative System and Inhibiting Ethylene Synthesis - Xiao, Yuansong; Wu, Xuelian; Sun, Maoxiang; Peng, Futian (Frontiers in Plant Science, 2020)
Peach (Prunus persica L. Batsch) is a shallow root fruit tree with poor waterlogging tolerance. Hydrogen sulfide (H2S) is a signal molecule which regulates the adaptation of plants to adverse environments. Nevertheless, the effects of exogenous applications of H2S in fruit tree species especially in peach trees under waterlogging stress have been scarcely researched. Thus, the goal of this research was to investigate the alleviating effect of exogenous H2S on peach seedlings under waterlogging stress. In the present study, we found that the effect of exogenous H2S depended on the concentration and 0.2 mM Sodium hydrosulfide (NaHS) showed the best remission effect on peach seedlings under waterlogging stress. Waterlogging significantly reduced the stomatal opening, net photosynthetic rate, and Fv/Fm of peach seedlings. The results of histochemical staining and physiological and biochemical tests showed that waterlogging stress increased the number of cell deaths and amounts of reactive oxygen species (ROS) accumulated in leaves, increased the number of root cell deaths, significantly increased the electrolyte permeability, O2.- production rate, H2O2 content and ethylene synthesis rate of roots, and significantly reduced root activity. With prolonged stress, antioxidative enzyme activity increased initially and then decreased. Under waterlogging stress, application of 0.2 mM NaHS increased the number of stomatal openings, improved the chlorophyll content and photosynthetic capacity of peach seedlings. Exogenous H2S enhanced antioxidative system and significantly alleviate cell death of roots and leaves of peach seedlings caused by waterlogging stress through reducing ROS accumulation in roots and leaves. H2S can improve the activity and proline content of roots, reduce oxidative damage, alleviated lipid peroxidation and inhibit ethylene synthesis. The H2S scavenger hypotaurine partially eliminated the effect of exogenous H2S on alleviating waterlogging stress of peach seedlings. Collectively, our results provide an insight into the protective role of H2S in waterlogging-stressed peach seedlings and suggest H2S as a potential candidate in reducing waterlogging-induced damage in peach seedlings.